Indonesia vs. Malaysia: The Battle for Border Territory Resolved - Ruhana, Siti; Karim, Tun Abdul (International Law Discourse in Southeast Asia, 2024)
This paper provides a comprehensive analysis of the resolution of the longstanding border dispute between Indonesia and Malaysia. The study delves into the complex dynamics of this conflict, offering insights into its historical context, the key issues at stake, and the eventual resolution reached between the two nations. The Indonesia-Malaysia border dispute has been a contentious issue for decades, marked by conflicting territorial claims and occasional tensions between the two neighboring countries. Rooted in historical and geopolitical factors, the dispute has encompassed various regions along the land border, including areas rich in natural resources and strategic importance. This paper examines the factors that fueled the dispute, ranging from historical grievances to economic interests and geopolitical considerations. It explores how these factors influenced the negotiation process and shaped the positions of both Indonesia and Malaysia. Central to the analysis is the discussion of the diplomatic efforts and mechanisms employed to address the dispute. From bilateral negotiations to third-party mediation, the paper evaluates the effectiveness of different approaches in facilitating dialogue and fostering cooperation between the two nations. Furthermore, the paper highlights the role of international law and norms in guiding the resolution process. It assesses how principles of territorial sovereignty, boundary delimitation, and peaceful dispute resolution were applied in reaching a mutually acceptable agreement. Finally, the study discusses the outcome of the resolution and its implications for Indonesia, Malaysia, and the broader region. It examines the terms of the agreement, including any concessions made by either party, and considers the potential impact on bilateral relations, economic development, and regional stability. By providing a nuanced analysis of the Indonesia-Malaysia border dispute and its resolution, this paper contributes to a deeper understanding of interstate conflicts and the mechanisms available for their peaceful resolution in Southeast Asia.